2021
DOI: 10.1016/j.ctro.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The changing role of radiation oncology professionals in a world of AI – Just jobs lost – Or a solution to the under-provision of radiotherapy?

Abstract: The changing role of radiation oncology professionals in a world of AI-Just jobs lost-Or a solution to the under-provision of radiotherapy?, Clinical and Translational Radiation Oncology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…This is inevitable as automation takes over some traditional tasks and generates new tasks to be undertaken by humans. A recent commentary addressed if AI will replace professionals in radiation oncology and reported that automation will not only replace many manual tasks performed today, increase efficiency and reduce the time spent on planning, but also create new opportunities [17]. Professional groups could feel threatened if changes in the work area involve redefinition of professional roles, in particular where it might be perceived as devaluation of established skills or contributions [13,18].…”
Section: Discussionmentioning
confidence: 99%
“…This is inevitable as automation takes over some traditional tasks and generates new tasks to be undertaken by humans. A recent commentary addressed if AI will replace professionals in radiation oncology and reported that automation will not only replace many manual tasks performed today, increase efficiency and reduce the time spent on planning, but also create new opportunities [17]. Professional groups could feel threatened if changes in the work area involve redefinition of professional roles, in particular where it might be perceived as devaluation of established skills or contributions [13,18].…”
Section: Discussionmentioning
confidence: 99%
“…RTTs are well poised to take on advanced practice roles crossing the barriers of standard operating procedures. Indeed, AI has facilitated a redistribution of tasks to promote efficiency and release ROs valuable time for other tasks that cannot be automated or delegated [42] . Whereby, AI OAR contouring has replaced RTT contouring, abet some leniency [8] and similarly RO delineation activities have been replaced by RTTs, if not AI segmented [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, AI has facilitated a redistribution of tasks to promote efficiency and release ROs valuable time for other tasks that cannot be automated or delegated [42] . Whereby, AI OAR contouring has replaced RTT contouring, abet some leniency [8] and similarly RO delineation activities have been replaced by RTTs, if not AI segmented [42] . Often clinicians are involved in credentialing and assessment of adaptive training techniques, assessing accuracy in skills and decision-making [7] , [28] .…”
Section: Discussionmentioning
confidence: 99%
“…We have read with great interest the work of Korreman S. et al regarding the use of Artificial Intelligence (AI) in the field of radiation oncology [1] . In our opinion, the main task of a radiation oncologist is to clinically evaluate patients for the best course of radiation and to carry out the treatment regimen with high precision.…”
Section: Introductionmentioning
confidence: 99%